2022
DOI: 10.1080/16549716.2022.2120251
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of child death in Jigawa State, Nigeria: a mixed-methods study on how sociocultural nuances shape paediatric mortality reporting

Abstract: Background Vital statistics are critical for effective public health and monitoring progress towards child survival. Nigeria has the highest global under-five mortality rate; however, deaths are often under- or misreported. Objective We explored perceptions of child deaths and socio-cultural factors influencing the reporting of child deaths in Jigawa State, Nigeria. Methods We conducted a triangulation mixed-methods study in Kiyawa local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We had reflected on this finding with our research team and a common report was caregivers attributing childhood illness to teething. While they reported that many caregivers believed teething would resolve spontaneously, we also observed caregivers attributing child death to teething in this setting ( 36 , 37 ). In our study, fever was associated with both care seeking and timely care seeking practices.…”
Section: Discussionmentioning
confidence: 58%
“…We had reflected on this finding with our research team and a common report was caregivers attributing childhood illness to teething. While they reported that many caregivers believed teething would resolve spontaneously, we also observed caregivers attributing child death to teething in this setting ( 36 , 37 ). In our study, fever was associated with both care seeking and timely care seeking practices.…”
Section: Discussionmentioning
confidence: 58%
“…Caregivers’ refusal of medical oxygen and willingness to allow the child to die in peace highlight the importance of culture and religion in healthcare service utilisation—particularly in northern Nigeria, where child death is typically perceived as an act of God. 61 The involvement of religious leaders may be particularly important when introducing new or poorly understood health interventions and services, such as oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because final decision-making around the intervention remained with the wider team, transformative participation was not achieved in this instance. However, as outlined in the results, learnings from the CCs also shaped the structure and content of the PLA intervention, the mode of delivery, as well as aspects of evaluation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%